Anemia prevalence and associated factors among school-children of Kersa Woreda in eastern Ethiopia: A cross-sectional study. - Kabtamu Gemechu; Haftu Asmerom; Lealem Gedefaw; Mesay Arkew; Tilahun Bete; Wondimagegn Adissu (PLoS ONE, 2023)
Background Anemia in school children is a worldwide public health problem, affecting about a quarter of this population. It also remains a significant problem in developing countries, with multifactorial causes. Anemia in school children has adverse effects on the development of the physical, cognitive, immunity of affected children, and subsequently their educational achievement which may lead to loss of productivity at a later age in life. Regular surveillance that could provide evidence-based local data is required to intervene in the problems. Therefore, this study aimed to determine the prevalence and associated factors of anemia among school children in primary schools of eastern Ethiopia. Methods School-based cross-sectional study was conducted by recruiting 482 school- children. Data on socio-demographic and dietary habits were collected from parents/legal guardians. Capillary blood for blood film preparation and hemoglobin measurement and stool sample for the diagnosis of intestinal parasites infection was collected. Hemoglobin concentration was measured using a hemoglobinometer HemoCue® 301+, and stool examination by direct wet mount and concentration technique. Data were entered into epi-data and exported into SPSS for analysis. Bivariate and multivariate logistic regression was run to identify associated factors. Association was described using adjusted OR (AOR) along with 95% CI and variables with a p-value<0.05 were considered statistically significant. Results The overall prevalence of anemia was 24.5%. Being female (AOR = 2.88, 95% CI: 1.69, 4.92), family size of more than 5 (AOR = 2.78, 95% CI: 1.60, 4.81), not consuming green leafy vegetables (AOR = 4.09, 95% CI: 2.42, 6.94), consumption of milk (AOR = 2.22, 95% CI: 1.27, 3.88), being stunting (AOR = 3.17, 95% CI: 1.70, 5.91) and parasite infections (AOR = 5.23, 95% CI: 2.77, 9.85) were significantly associated with anemia. Conclusion In this study nearly one-fourth of children were anemic. Anemia was a moderate public health problem among schoolchildren in the study area. Thus, school-based interventions targeting nutritional factors and intestinal parasite infection need to be implemented.